Development of intelligent automated driving control system (lateral control) - Yang, S.Y.; Park, S.T.; Jeong, J.H.; Park, B.R. (1999 3rd Russian-Korean International Symposium on Science and Technology, 1999)
An automated driving control system consists of lateral control and longitudinal control. The former controls the steering angles to keep a stable position and the latter controls vehicle speed. In the paper, for lateral control, a vehicle dynamic model with a lane-keeping method is built up and a lateral control algorithm is proposed. In order to verify the feasibility of the algorithm, a system is constructed in a vehicle for steering control, then the lateral control algorithm is simulated to determine whether it is suitable for real situations or not. The simulation results confirm that the proposed lateral algorithm is well suited to real situations.